PENGARUH KECERDASAN INTERPERSONAL TERHADAP PENYESUAIAN DIRI SISWA MTsN 2 MEDAN - Nurul Aini Nasution; Ahmad Syarqawi (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
Interpersonal intelligence possessed by a student is very influential in adjusting to the surrounding environment. Students with high interpersonal intelligence have the potential to become leaders in dealing with a problem or dispute that occurs with their friends. Adjustment is a demand that everyone must own. With the adjustment, a person can carry out his activities properly. This study aimed to gain knowledge about the effect of interpersonal intelligence on the self-regulation of class VIII MTsN 2 Medan. Data collection used the interpersonal intelligence and self-adjustment scale, which the researchers tested for validity and reliability using a random sampling technique with a total sample of 27 class VIII students of MTsN 2 Medan. The research method uses quantitative research with an ex-post facto design. Data analysis used a simple regression analysis test. The results of the data analysis showed a significant correlation value of 0.000 and an R-square of 0.474. The study's results prove that interpersonal intelligence significantly affects the self-adjustment of class VIII MTsN 2 Medan.